Experimental Study on the Effect of Triangular Plate Barrier Height on Flow Velocity Distribution in Open Channels - Lhiung Phung Hwa (Newinera Publisher, 2021)
Open and closed channel flow flows are distinct, the flow in the channels will constantly change. The flow will also be altered if the water level or flow velocity changes. It was found that employing the Pitot Tube Portable yielded findings identical to those calculated by other methods. A water transfer system is made up of natural or artificial structures via which water is moved from one site to another. The carrier building may be open or closed, depending on whether you want to utilize it as a shipping or receiving location. An open channel with a relatively narrow opening at the top is known as an open conduit. The speed data collection technique is carried out vertically, with a review point as illustrated above. The velocity of the flow was measured using a Pitot Tube Portable Automatic tool. The results are entered into the Froude number (fr) after each review point to determine the type of velocity flow at each Review point. The normal flow velocity distribution pattern emerges at the measurement sites of 450 cm, 500 cm, and 550 cm.